Investigation of prostate specific antigen glycosylation - Marinović Vesna (Journal of the Serbian Chemical Society, 2000)
In the present work, prostate specific antigen (PSA) glycosylation was examined by lectin affinity methods. The results obtained indicated that PSA purified from human seminal plasma contained at least one bianntenary N-linked oligosaccharide chain, which was composed of the monosaccharides manose, galactose, N-acetylgalactosamine, fucose and sialic acid. No O-linked carbohydrate chains were detected.